Sexual Violence and Women's Work in Early Modern Drama and Poetry - Rizzi, James. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of English.; Advisor: Judith Haber.; Committee: Jess Keiser, Kevin Dunn, and Coppélia Kahn.; Keyword: English literature.